УСТАЗ ФАХРИДДИН САДИҚОВТЫҢ ӨМИР ЖОЛЫ ҲӘМ ДӨРЕТИЎШИЛИГИ - Жуманиязов, И.Р. (FAN va JAMIYAT, 2024)
In the article, the author gives the information about the teachers, the educational process, career, created works, awards of the famous musician, composer Fakhriddin Sadikov on the Chang musical instrument.